13.0k views
4 votes
Find,in ascending powers of x, the first 3 terms of the expression (1+kx)⁴ (1-4x)³.If the coefficient of x is zero, find the value of k and the coefficient of x².

1 Answer

5 votes

Final answer:

To find the first three terms of the expression (1+kx)⁴ (1-4x)³, we need to expand the expression using the binomial theorem. The first three terms are 1, (4k-12k)x, and (6k²-48k²+12k)x². To find the coefficient of x², we set the expression (6k²-48k²+12k) equal to zero and solve for k. The value of k is 1/3.

Step-by-step explanation:

To find the first three terms of the expression (1+kx)⁴ (1-4x)³, we need to expand the expression using the binomial theorem.

First, let's expand (1+kx)⁴ using the binomial theorem:

(1+kx)⁴ = 1 + 4kx + 6k²x² + 4k³x³ + k⁴

Now, let's expand (1-4x)³ using the binomial theorem:

(1-4x)³ = 1 - 3(4x) + 3(4x)² - (4x)³

Multiplying the two expanded expressions:

(1+kx)⁴ (1-4x)³ = (1 + 4kx + 6k²x² + 4k³x³ + k⁴)(1 - 3(4x) + 3(4x)² - (4x)³)

Expanding further:

(1+kx)⁴ (1-4x)³ = 1 + 4kx + 6k²x² + 4k³x³ + k⁴ - 12kx - 48k²x² - 48k³x³ + 12kx² + 48k²x³ - 12k³x⁴

Combining like terms:

(1+kx)⁴ (1-4x)³ = 1 + (4k-12k)x + (6k²-48k²+12k)x² + (4k³-48k³)x³ - 12k³x⁴

The first three terms of the expanded expression are:

1, (4k-12k)x, (6k²-48k²+12k)x²

To find the coefficient of x², we need to look at the expression (6k²-48k²+12k). Since the coefficient of x² is zero, we can set this expression equal to zero and solve for k:

6k²-48k²+12k = 0

Combining like terms:

-42k² + 12k = 0

Factoring out k:

k(-42k + 12) = 0

Setting each factor equal to zero:

k = 0 or -42k + 12 = 0

If k = 0, the coefficient of x² is also zero.

Solving -42k + 12 = 0 for k:

-42k = -12

k = -12/-42

k = 1/3

If k = 1/3, the coefficient of x² is also zero.

User Pedro Lopes
by
7.5k points